The Importance of Learning The Philosophy of Christian Religious Education in Theological Colleges - Mau, Marthen; Kainara, Semi Darius; Marampa, Elieser R. (East Asian Journal of Multidisciplinary Research, 2024)
Teaching the philosophy of Christian religious education to theology students is not wrong and sinful, but something that is beneficial for oneself and for building up others. For this reason, teaching PAK philosophy is very important to be taught to Christian theology students in theological schools. The application of PAK philosophy learning for theology students is very important in order to obtain wise thoughts, feelings and hearts because philosophy talks about wisdom. PAK philosophy learning has a direct relationship with the teachings of the Christian Scriptures. Therefore, the Holy Bible is the main standard in studying PAK philosophy.